High Sensitive Troponin I and Extended Range C-Reactive Protein as Markers to Predict Cardiotoxicity in Locally Advanced Breast Cancer with Neoadjuvant CAF (Cyclophoshpamide, Adriamycin/Doxorubicin, 5Fluorouracil) Therapy - Hidayat, Yusfik Helmi; Ishardyanto, Hantoro; Anniwati, Leonita (Folia Medica Indonesiana, 2020)
The limitation of echocardiography to measure chemotherapy cardiotoxicity at left locally advanced breast cancer with large ulcer is still serious problem. HsTnI and erCRP are biomarkers to detect cardiotoxicity that are cheap, easy to examine and available at Dr.Soetomo Hospital Surabaya. This study was to compare HsTnI, erCRP and echocardiography as cardiotoxicity predictors in locally advanced breast cancer with neoadjuvant CAF therapy. This study used one group pretest and posttest design among 23 locally advanced breast cancer patients. All patients underwent echocardiography, HsTnI, and erCRP examinations before and after 3 times chemotherapy and compared. The average age was 49.78±8.7. Statistically significant decrease in LVEF was found after treatment (67.98%±4.06 and 64.07%±3.53, p=0.000). HsTnI was significantly increased after treatment (0.007 µg/mL±0.004 and 0.043 µg/mL±0.051 p=0.000). erCRP was significantly decreased after treatment (1.043mg/dL±0.913 and 0.573mg/dL±0.444 p=0.044). Decreased LVEF and increased HsTnI was compared by its cardiotoxic cut-off. HsTnI was significantly better and faster to detect cardiotoxicity (0.033±0.051 p=0.002). In conclusion, strong correlation is present in the detection of cardiotoxicity between HsTnI and LVEF. HsTnI is faster than echocardiography, and could be alternative diagnostic to detect early cardiotoxicity.